Tabularia kobayasii: a new araphid diatom (Bacillariophyta, Fragilariaceae) from Japan - Suzuki, Hidekazu; Mitsuishi, Kyoko; Nagumo, Tamotsu; Tanaka, Jiro (Phytotaxa, 2015)
A new species of Tabularia, T. kobayasii, was found on seaweeds collected from several estuaries in the Central Pacific coast of Japan. Its morphology was examined by light and scanning electron microscopy; details are described herein. This araphid diatom is characterized by: 1) tufted or band-like colony; 2) valves lanceolate, flat with steep mantle, striae consisting of cribrate areolae, a wide lanceolate sternum, single rimoportula, and an occelulimbus at both poles; and 3) a cingulum consisting of a few non-fimbriated girdle bands including the valvocopula.